Wednesday

April 23, 2014

April 23, 2014

Posted by **Ann** on Wednesday, July 7, 2010 at 12:44pm.

y=4(x+3)-2x

y=4x+3-2x

y=2x+3

2x+3=y

2x=y-3

x=y/2-3

Hopefully I have rearranged the formula y=4(x+3)-2x to express x in terms of y.

- Math -
**drwls**, Wednesday, July 7, 2010 at 2:48pmThe first step is wrong

4(x+3) does not equal 4x + 3.

- Math -
**Henry**, Wednesday, July 7, 2010 at 3:03pmY-4(X+3)-2X

Y=4X+12-2X

Y=2X+12

2X=Y-12

X=Y/2-6

**Related Questions**

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...

TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

check my work on derivatives - Can someone check my work? So, I took the ...

math-calculus - i think i do something wrong again(2x+1)/(x-3)-(4x-1)/(2x-3) = 0...

alegebra - 1. What is the factored form of 4x 2 + 12x + 5? (1 point) (2x + 4)(2x...

Algebra - Need help with this problem, 2x+y=6 solve for y 2x+y=6 subtract 2x ...

Math - Write the equation in standard form using integers. Can someone please ...

Math - Please show the solutions! 1.) x+y-2(2x-3y) 2.) x+y/2 - 3x-y/4 + x-5y/8 3...